Meriones unguiculatus infected by Haemonchus contortus: Evaluation of different experimental protocols - Gressler L.T. (2019)
© Cambridge University Press 2018.Many important studies on resistance reversion, anthelmintic efficacy and, especially, new molecules with antiparasitic effects are performed in laboratories using gerbils (Meriones unguiculatus) as the experimental model. This study aimed to evaluate the use of corticosteroids (dexamethasone and methylprednisolone acetate) in gerbils experimentally infected with different doses of infective larvae (sheathed or exsheathed) of Haemonchus contortus. In the first experiment, 28 gerbils were divided into seven groups infected by 2-6 × 103 larvae, with or without immunosuppression using corticosteroids. In the second experiment, eight gerbils were divided into two groups infected by 2 × 103 sheathed or exsheathed larvae. For the third assay, seven immunosuppressed gerbils were infected with 2 × 103 sheathed larvae and were killed 15 days post infection (PI). The highest number of parasites was recovered from methylprednisolone-immunosuppressed animals. We observed red and white blood cell alterations and biochemical parameters in infected animals that had undergone immunosuppression with methylprednisolone. We highlight that in the first and second experiments a satisfactory number of worms was recovered using sheathed larvae and immunocompetent animals. When exsheathed larvae were used, the number of worms recovered was unsatisfactory. A considerable larval burden was recovered from immunosuppressed gerbils 15 days PI, and body weight did not influence establishment of larvae.